Religious Moderation in Pesantren-Based Islamic Higher Education: An Institutional Structuration Analysis from East Java, Indonesia - Erfan Efendi; Moh. Rofid Fikroni; Ali Saeed; Mohammad Zakaria Drajat Dahlan (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
This study examines how religious moderation is structured and sustained within pesantren-based private Islamic higher education institutions (Perguruan Tinggi Keagamaan Islam Swasta/PTKIS) in the Tapal Kuda region of East Java, Indonesia. It specifically explores the roles of institutional leadership, organizational culture, and everyday academic practices in the institutionalization of moderation. This research employed a qualitative interpretive design involving six pesantren-based PTKIS. Data were collected through in-depth interviews, non-participant observations, and document analysis with 10 key informants, including university leaders, pesantren authorities, and academic managers. The data were analyzed using a structuration perspective to examine the dynamic interaction between institutional structures and human agency in reproducing moderation practices. The findings show that religious moderation is sustained through a hybrid governance model that combines formal university administration with pesantren-based religious authority. Within this model, moderation is institutionalized through three interconnected mechanisms: authoritative regulation grounded in leadership legitimacy, persuasive academic engagement through dialogical pedagogy, and normative cultural internalization through pesantren routines and mentoring practices. The originality of this study lies in the development of an institutional structuration perspective that conceptualizes religious moderation as a recursively reproduced institutional practice rather than merely a policy agenda or ideological discourse. This study contributes theoretically by offering a three-mechanism model for understanding the institutional reproduction of religious moderation in Islamic higher education and contributes practically by providing insights for policymakers and university leaders on how culturally embedded governance and leadership legitimacy can strengthen the sustainability of religious moderation.